Metamorphic pressure variation in a coherent Alpine nappe challenges lithostatic pressure paradigm - Cindy Luisier (Nature Portfolio, 2019)
The geodynamic evolution of mountain ranges can be reconstructed using the pressure recorded by minerals in metamorphic rocks, under the key assumption that rock pressure is lithostatic. Here, the authors challenge the lithostatic pressure paradigm by showing that there can be significant outcrop-scale pressure gradients due to compression- and reaction-induced stress.